Implementasi Manajemen Strategi Guru Profesional di Madrasah Ibtidaiyah Swasta Mawaddah Gebang - Sri Indarti; Rani Febriani (Tut Wuri Handayani : Jurnal Keguruan dan Ilmu Pendidikan, 2022)
The problem in this study shows that there are still many teachers who are not motivated to improve their professionalism, this is because of the facilities and infrastructure at Madrasah MIS Mawaddah. This type of research is qualitative with the Research filed approach. Methods of collecting data by means of observation, interviews and documentation. Data validity test techniques include data credibility test (internal validity), data dependability (reliability) test, transferability test (external validity/generalization), and confirmability test (objectivity). The results of this study indicate that the process of implementing professional teacher management strategies at MIS Mawaddah Gebang has been carried out well, starting with the planning stage, the planning is determined by the Head of Madrasah taking into account the evaluation results in previous years. After all activities are designed, the next process is organizing. The first thing to do is to classify tasks according to the resources they have. Then proceed with the division of tasks, at this stage grouping activities are also carried out. The results of interviews and observations of researchers indicate that activities related to the application of administrative management in supporting student academic services are divided into 3 (three) parts, namely new student admissions, teaching and learning activities, and graduation. After the division of tasks and grouping of activities, the most important thing that must be considered by the leadership is the process of action.